Determination Of Soil Moisture Content Using Pulse Infrared Radiation - Ahmad, Suzilasahibatul Akhmal (2003)
Moisture content determination is a routine laboratory test to determine the amount of water present in a quantity of soil sample. It is normally being expressed in terms of the dry mass of soil. The standard practice for moisture content determination of soil can be determined, e.g., using electrical oven (ASTM D 2216) or microwave oven (ASTM D 4643). This study presents a unique equipment developed for the determination of soil moisture content using far infrared radiation (FIR). The pulse infrared radiation is generated by passing the conventional electric heater tube through a thin film of specific powdered ceramic radicals. By applying experimental design matrix to minimise the number of test and using SPSS Programme to analyse the linear regression, the formula of time for complete drying is compared to the time measured in experiment. The correlation of time by formula and time measured proved the reliability of the formula developed in this study. Throughout the study, the results of time in moisture content determination using the application of FIR ranges from 20 minutes (0.33 hour) to 180 minutes (3 hour). The developed equipment can also be used for rapid moisture content determination. This is particularly useful for high volume repeated testing such as in highway construction.